1977
DOI: 10.2307/3225669
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Natural and Artificial Substrate Colonization by Scanning Electron Microscopy

Abstract: 1977. Evaluation of natural and artificial substate colonization by scanning electron microscopy. Trans. Amer. Micros. Soc., 96: 506-519. Progressive microbial colonization of natural (sycamore leaf) and artificial (polyurethane foam) substrate material in lotic and lentic systems was studied by scanning electron microscopy. The organisms which participated in colonization showed substrate preferences and aquatic system variation. The rate of colonization was dependent not only on the aquatic system, but also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

1980
1980
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 28 publications
2
11
0
1
Order By: Relevance
“…Furthermore, it was quite noteworthy that pennate diatoms only showed significant colonization in those regions where mycelial matrices were first established. Similar colonization patterns associated with bacterial slime and hyphal networks were observed by Paul et al (1977) and Geesey et al (1978). It has also been suggested that these organic aggregations are of nutritional significance to microbial colonizers (Pearl, 1974;Pearl et al, 1975;Paul et al, 1977).…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Furthermore, it was quite noteworthy that pennate diatoms only showed significant colonization in those regions where mycelial matrices were first established. Similar colonization patterns associated with bacterial slime and hyphal networks were observed by Paul et al (1977) and Geesey et al (1978). It has also been suggested that these organic aggregations are of nutritional significance to microbial colonizers (Pearl, 1974;Pearl et al, 1975;Paul et al, 1977).…”
Section: Resultssupporting
confidence: 53%
“…Similar colonization patterns associated with bacterial slime and hyphal networks were observed by Paul et al (1977) and Geesey et al (1978). It has also been suggested that these organic aggregations are of nutritional significance to microbial colonizers (Pearl, 1974;Pearl et al, 1975;Paul et al, 1977). The potential of a relatively similar nutrient base made available on each rock surface by the accumulation of organic aggregates would further reduce any subtle preferences displayed by diatom taxa for micro-physical surface features.…”
Section: Resultsmentioning
confidence: 66%
“…The microbiota colonizing the foam substrates was a heterogenous assemblage of algae, bacteria, fungi, microcrustacea, and protozoans . The substrates were colonized by both autotrophic and heterotrophic free-swimming, sessile and attached forms and contained a similar variety of species as were found in natural Cedar Run substrates (Matthews, 1981 ;Paul et al, 1977) . Uniform sized substrates (5 x 6 .5 x 7 .5 cm) were presoaked in distilled water for 24 h, then tied with cotton twine to permanent anchors at each station .…”
Section: Study Areamentioning
confidence: 99%
“…Abschnitt 4.1 und Abschnitt 4.3), können aber auch komplementär durch Pyrolyse-GC-MS an isolierten Partikeln bestimmt werden (Fries et al 2013;Dekiff et al 2014;Nuelle et al 2014 (Zettler et al 2013;Eich et al 2015), während sich in marinen Sedimenten und Flusswasser überwie gend Prokaryonten ansiedelten (Harrison et al 2014;McCormick et al 2014;Nauendorf et al 2016). Bei der Exposition von PU-Schaum in Fluss-und Teich wasser dominierten Algen den Biofilm (Paul et al 1977). Durch die Probenvorbereitung für die klassische Rasterelektronenmikroskopie bleibt aber die feuchte dreidimensionale Struktur des Biofilms nicht erhalten.…”
Section: Qualitative Und Quantitative Analyse Von Mikroplastik In Umwunclassified